The Effect of Return On Equity (ROE) and Earning Per Share (EPS) On Share Prices - Sekar Putri Choiri; Achmad Agus Yasin Fadli (Indonesian Development of Economics and Administration Journal, 2023)
This study aims to determine the simultaneous and partial effect of the independent variables, namely Return On Equity (ROE) and Earning Per Share (EPS) on the dependent variable, namely stock prices. This research was conducted at PT Unilever Indonesia Tbk. The type of research used in this research is causal associative research. The population used in this study is the company’s financial report data in the form of balance sheets and profit and loss statements for 10 years, namely 2013 to library or secondary studies. The data analysis technique used is multiple regression, classic assumption test, t test, f test, and the coefficient of determination. Based on the research results, it can be concluded that simultaneously Return On Equity (ROE) and Earning Per Share (EPS) have a significant effect on stock prices at PT Unilever Tbk, partially Return On Equity (ROE) have no significant effect on stock prices at PT Unilever Tbk Period 2013-2022, Based on the results, Return On Equity has a tcount that is smaller than ttable -0.360 <2.364 and a significant value that is greater than a significance value of 0.730 > 0.05 , Earning Per Share has a tcount that is smaller than ttable -4.251 <2.364 and a significant value that is greater compared to the significance of 0.004 <0.05, it can be concluded that the results of Fcount 22.533 <Ftable 4.74 and systematically obtained significant results of 0.001 <0.05.